Sodium Ingestion Improves Groundstroke Performance in Nationally-Ranked Tennis Players: A Randomized, Placebo-Controlled Crossover Trial - Munson, Edward H.; Orange, Samuel T.; Bray, James W.; Thurlow, Shane; Marshall, Philip; Vince, Rebecca V. (Frontiers in Nutrition, 2020)
This study examined the dose response effects of ingesting different sodium concentrations on markers of hydration and tennis skill. Twelve British nationally-ranked tennis players (age: 21.5 ± 3.1 years; V̇O2peak: 45.5 ± ml.kg.min-1) completed four identical in-door tennis training sessions in a cluster randomised, single-blind, placebo-controlled, crossover design. Twenty-minutes prior to each training session, participants consumed a 250 ml sodium-containing beverage (10, 20, 50 mmol/L) or a placebo (0 mmol/L), and continued to consume 1000 ml of the same beverage at set periods during the one-hour training session. Tennis groundstroke and serve performance, agility, hydration status (urine osmolality), fluid loss, sodium sweat loss and perceptual responses (rating of perceived exertion (RPE), thirst, and gastrointestinal (GI) discomfort) were assessed. Results showed that ingesting 50 mmol/L sodium improved hydration status (-119 mOsmol/kg; p = 0.037) and groundstroke performance (5.4; p < 0.001) compared with placebo. This was associated with a reduction in RPE (-0.42; p = 0.029), perception of thirst (-0.58; p = 0.012), and GI discomfort (-0.55; p = 0.019) during the 50 mmol/L trial compared with placebo. Linear trend analysis showed that ingesting greater concentrations of sodium proportionately improved hydration status (β = -147 mOsmol/kg; p = 0.007) and groundstroke performance (β = 5.6; p < 0.001) in a dose response manner. Perceived thirst also decreased linearly as sodium concentration increased (β = -0.51; p = 0.044). There was no evidence for an effect of sodium consumption on fluid loss, sweat sodium loss, serve or agility performance (p > 0.05). In conclusion, consuming 50 mmol/L of sodium before and during a 1-hour tennis training session improved hydration status and groundstroke performance in nationally-ranked tennis players. There was also evidence of dose response effects, showing that ingesting greater sodium concentrations resulted in greater improvements in hydration and groundstroke performance. The enhancement in tennis skill may have resulted from an attenuation of symptomologic distracters associated with hypohydration, such as RPE, thirst and GI discomfort.